2018
DOI: 10.1111/vsu.12964
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implementation of a surgical safety checklist on perioperative and postoperative complications at an academic institution in North America

Abstract: Objective To evaluate the efficacy of a surgical safety checklist (SSC) in reducing perioperative and postoperative complications. Study design Before‐and‐after intervention study. Animals Client‐owned dogs (n = 633) and cats (n = 44). Methods Consecutive surgeries were enrolled in the study. The “before” phase consisted of 267 surgeries performed without an SSC (SSC−) followed by 75 SSC− surgeries in which a trained observer was in the operating room to detect possible complications. An SSC was then implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 26 publications
3
25
1
1
Order By: Relevance
“…In the paper by Cray et al, a decrease in SSI was detected following commencement of the checklist. 8 Their reported prechecklist rate of SSI was 7.9%, while the prechecklist rate of SSI in our population was 2.5%. Some of the processes in place at our institution prior to commencement of the checklist may explain this low rate of SSI, potentially affecting the ability to further prevent this complication with implementation of additional preventive measures, such as a checklist.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…In the paper by Cray et al, a decrease in SSI was detected following commencement of the checklist. 8 Their reported prechecklist rate of SSI was 7.9%, while the prechecklist rate of SSI in our population was 2.5%. Some of the processes in place at our institution prior to commencement of the checklist may explain this low rate of SSI, potentially affecting the ability to further prevent this complication with implementation of additional preventive measures, such as a checklist.…”
Section: Discussioncontrasting
confidence: 60%
“…A study focused on the effects of a SC in academic veterinary medicine 8 included 677 animals, 342 animals in the prechecklist group and 335 animals in the postchecklist group. 8 That study concluded that implementation of a SC decreased the odds of perioperative and postoperative surgical complications from 40.9% to 29.3%. This change included a reduction in the rate of postoperative SSIs from 7.9% to 3.0%.…”
Section: Introductionmentioning
confidence: 99%
“…, Cray et al . ). The checklist used in our hospital was a modified version of the WHO checklist and was designed by two individuals.…”
Section: Discussionmentioning
confidence: 97%
“…11,12,13 Veterinary literature related to the application of SSC has largely focused on its influence on animal morbidity rather than on implementation strategies. [14][15][16][17][18] Improved postoperative outcomes have been documented after implementation and consistent use of SSC in clinical settings. [14][15][16] However, the inconsistent uptake of SSC documented in the human literature justifies exploration of implementation strategies in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Improved postoperative outcomes have been documented after implementation and consistent use of SSC in clinical settings. [14][15][16] However, the inconsistent uptake of SSC documented in the human literature justifies exploration of implementation strategies in veterinary medicine. 19 Barriers identified in the human research may prove a useful benchmark for effective implementation of SSC, but it is hypothesized that veterinary organizational and cultural differences may nuance the experience.…”
Section: Introductionmentioning
confidence: 99%